Acute diffuse and transient thyroid swelling after intravenous thrombolysis for acute ischemic stroke: A case report. Issue 36 (September 2018) - Shi, Liuhong; Yan, Caoxin; Xu, Wen; Huang, Pintong
Abstract: Rationale: Intravenous thrombolysis is the primary therapy for acute ischemic stroke (AIS), but it has some complications, including symptomatic intracranial hemorrhage, orolingual angioedema, and extracranial bleeding. However, thyroid disorders associated with thrombolysis are very rare. Patient concerns: A 56-year-old man developed acute pain and neck swelling after thrombolysis with recombinant tissue plasminogen activator. Diagnoses: Ultrasound revealed a diffusely enlarged thyroid with linear hypoechoic areas throughout the entire gland, resembling a "cracked" appearance. Interventions: The patient was treated conservatively with cold packs and observed closely. Follow-up ultrasound was made. Outcomes: A few hours later, pain and swelling disappeared completely. A repeat ultrasound revealed complete recovery of thyroid volume and aspect on the next day. Lessons: After intravenous thrombolysis for AIS, several life-threatening complications, such as hemorrhage and orolingual angiedema, also can cause neck swelling. Urgent intubation and surgery may be required. However, the rare complication, acute diffuse thyroid swelling, is self-limiting and nonfatal and conservative treatment is sufficient. Neck ultrasound is helpful in rapidly distinguishing these complications.